Comprehensive Insights into Smart Contracts: Architecture, Sectoral Applications, Security Analysis, and Legal Frameworks - Farah Mazlan; Nur Faizah Omar; Nik Nor Muhammad Saifudin Nik Mohd Kamal; Ahmad Anwar Zainuddin (Journal of Informatics and Web Engineering)
Most conventional contract systems have issues with middlemen, drawn-out implementation procedures, fraud risk, and human error. Considering this, the project uses smart contract technology to provide a decentralized, automated, and safe solution in an effort to address such inefficiencies and the trust issues they raise. Smart contracts enable self-execution of contracts whose conditions are expressed explicitly in lines of code by presenting solutions using blockchain technology. The concept behind a smart contract is that each party may carry out their portion of the duties without depending on a third party and the contract will automatically execute in the meantime. This automation significantly reduces transaction costs while simultaneously improving security and transparency. With the use of this underlying technology, smart contracts may be used to directly code parties' compliance with their duties under the agreement and the blockchain will keep an immutable record of every transaction. For smooth and dependable transactions, smart contracts offer a dependable and effective substitute for conventional contract methods. Furthermore, integrating smart contracts with cutting-edge technologies like machine learning and artificial intelligence could improve decision-making and accelerate operations in a variety of sectors. Their application extends beyond financial transactions to areas such as supply chain management, energy trading, and healthcare, showcasing their versatility. Despite these advantages, issues like energy consumption, scalability, and regulatory compliance still need creative solutions. Ongoing research and development aim to address these issues, fostering the evolution of smarter, more sustainable contract systems. By leveraging these advancements, smart contracts keep opening the door for a revolution in the digital economy that will increase productivity and confidence.